Porcine reproductive and respiratory syndrome update: National situation and research progress - Ramírez P., Esteban (Avances en Ciencias Veterinarias, 2005)
Porcine reproductive and respiratory syndrome (PRRS) is an emerging viral disease in swine and considered the single most economically important disease of pigs worldwide, which causes highly contagious severe disease with a spectrum of states ranging from respiratory failure in neonates and nursery pigs to reproductive failure in pregnant gilts and sows. PRRSV is endemic to most swine producing countries and imposes a heavy economic burden due to high mortality associated with the disease. In Chile, the disease was recognized at the beginning of the year 2000, and rapidly a control and eradication program was developed by the government and the private enterprises. Since the recognition of the disease to the present time, innumerable groups of investigators have formed around the world, which has been translated in an immense amount of scientific information. In Chile the research has been focused to characterize the respiratory disease caused by the virus and the mechanisms of transmission and excretion, in order to obtain more data on the pathogenesis of the chilean isolate. In the following article will be presented an updated revision of the main etiological aspects, clinical, pathological, epidemiological and diagnostic tests of the disease. Moreover it will be analyzed the national situation, from the detection of the virus to the control measures and the eradication program taken by the authorities. Finally there are presented the preliminary results from the investigations that are being made with the isolated Chilean of the PRRSV.